Mechanisms of beneficial effects of DPP-4 inhibitors as a promising perspective for the prevention/treatment of the disruption of cardio-cerebrovascular homeostasis - Katarina Tomović Pavlović; Marko Anderluh; Andrija Šmelcerović (Frontiers in Pharmacology)
Cardio-cerebrovascular diseases are increasingly prevalent worldwide, with pathological changes in the heart and brain reinforcing each other. Diabetes is a major driver of comorbidity between these two systems and contributes to poor clinical outcomes. This review summarizes current evidence on shared risk factors and underlying mechanisms, with a particular focus on the role of dipeptidyl peptidase-4 (DPP-4) inhibitors as a potential therapeutic strategy for preserving cardio-cerebrovascular homeostasis. Growing evidence suggests that DPP-4 inhibitors offer benefits beyond glycemic control. These include improvements in endothelial function, reduction of oxidative stress and inflammatory responses, modulation of lipid and glucose metabolism, and regulation of blood pressure. Together, these actions support the anti-atherosclerotic and anti-thromboembolic properties of this drug class. These effects occur through both indirect pathways, via improved glycemic control, and direct cellular and molecular mechanisms. Although DPP-4 inhibitors are commonly used as second- or third-line agents in combination with other antidiabetic drugs, they have distinct advantages in specific populations. Notably, they are among the few hypoglycemic agents that are safe and effective in patients with impaired renal function—where the use of agents like metformin and SGLT-2 inhibitors is often contraindicated. In addition, DPP-4 inhibitors have shown favorable outcomes in elderly patients, particularly those aged 65 years and older. From a cardiovascular perspective, DPP-4 inhibitors have demonstrated protective effects against ischemic stroke, improved neurovascular function, and a reduction in major adverse cardiovascular events (MACEs). Importantly, they do not increase the risk of heart failure, unlike some other antidiabetic medications. While most cardiovascular outcome trials (CVOTs) involving DPP-4 inhibitors have shown neutral results, these studies were primarily designed to establish safety rather than demonstrate cardiovascular superiority. In conclusion, the pleiotropic effects, favorable safety profile, and suitability for vulnerable populations position DPP-4 inhibitors as promising agents in the management of cardio-cerebrovascular complications in diabetes. Further long-term, controlled clinical studies are warranted to fully establish their therapeutic potential across broader indications.